CRITICAL DISCUSSION ANALYSIS IN ONLINE NEWS TEMPO. CO ABOUT PILPERS 2019 (ANALISIS WACANA KRITIS PADA BERITA ONLINE TEMPO. CO TENTANG PILPERS 2019) - Pramita, Candra; Ramadan, Syahrul; Tressyalina, Tressyalina; Afnita, Afnita (Jurnal Gramatika, 2019)
Discourse analysis on Tempo online media. Co about PILPERS 2019 where a group or person is marginalized in the discourse. The purpose of this study is to describe the use of inclusion theory on political news and see the journalists' impartiality in the 2019 election in Tempo.co online news media. Data collection is done through three stages, (1) reading and understanding the discourse on Tempo's online mass media political news. The May 2019 edition of the Co with the aim of obtaining a clear understanding of the content of the discourse to be studied, (2) marking parts of discourse related to Leeuwen's inclusioan theory, and (3) inventorying sentences in discourses related to Leeuwen's inclusioan theory by sorting and grouping data. Analyzing data is done descriptively. Based on the results of the study it can be concluded, Leeuwen's inclusioan theory was found in eight Tempo mass media online news media. The May 2019 edition of Co consists of five of the seven existing theories, namely objectivity, nominations, nominations, identification, assimilation-individualization, and association-dissociation. Of the five Leeuwen inclusioan theories found there were 66 sentences containing Leeuwen's inclusioan theory. So, it can be concluded that in writing news about criminal journalists marginalizing victims. Journalists side with actors or actors. This can be seen from the way the journalists clearly portray the perpetrators and victims.